Successful epilepsy surgery for tuberous sclerosis complex evaluated by stereoelectroencephalography. Issue 5 (24th November 2020) - Fong, Choong Yi; Bleasel, Andrew; Dexter, Mark AJ.; Lawson, John A.; Wong, Chong H.
Abstract: Evaluating the candidacy for epilepsy surgery in patients with tuberous sclerosis can be challenging, particularly when non‐invasive investigations do not show a clear epileptogenic zone. Stereoencephalography may be useful in such cases. We present a case in which the primary epileptogenic tuber was successfully identified by stereoencephalography, which resulted in seizure freedom following epilepsy surgery. [ Published with video sequences ].